Policy Recommendation: In Developing the Potential of Bandur Picak Village, Koto Kampar Hulu, Kampar Regency - Bunga Chintia Utami; Lapeti Sari; Taryono Taryono; Mahardi Mahardi (Jurnal Public Policy, 2022)
This study aims to look at policy recommendations for developing village potential in Bandur Picak Village, Koto Kampar Hulu District, Kampar Regency, and to find out alternative policies that have been implemented, especially in the management of the Larangan River. Many models are available in the policy recommendations. One of them is a simple model, an analytical model used only to choose to remain in the old condition/action (status quo) or choose a new series of activities/actions as an alternative policy. The method in this research is descriptive qualitative, with data sources in the form of primary data and secondary data. Preliminary data were sourced from the village head, sub-district head, the Kampar Regency Village Empowerment Service, and the community. Informants will be selected through a purposive sampling technique. At the same time, secondary data is obtained from written sources such as village profile books, BPS data, and so on. Data collection techniques used in this study were intensive observation, in-depth interviews, documentation techniques, and a literature study. The results of this study are expected to be a reference for policy recommendations in developing village potential using the same model